THE PHILOSOPHY OF INTUITIONIST MATHEMATICS - S.I. MASALOVA (Advanced Engineering Research, 2006)
The article covers the main problems of intuitionist mathematics which appeared in the late 19th century-early 20th century. Among them are the problems of existence in mathematics, the problem of substantiation of mathematics, epistemological methods of mathematical objects construction, methodology of mathematics and others. Such stages of mathematical theory development as half-intuitionism, intuitionism proper and ultra-intuitionism are considered.